Modi doctrine : science diplomacy - Sikka, Pawan ed. (New Delhi Synergy Books, 2019)
Dr. Pawan Sikka (b. 1944) is a former Scientist-G, Advisor, Government of India, Department of Science and Technology (Ministry of Science and Technology) New Delhi. Prior to it as Director (International Relations) for about 7-8 years, he coordinated the Bilateral and Multi-lateral programmes of Iwo international cooperation towards extending the frontiers of new and emerging fields in science and technology. He was Leader of the Indian delegation to SAARC Group Meeting on Science and Technology at Dhaka, Bangladesh, in 1995. He has received his M.Sc., Ph.D. as well as, D.Sc. degrees in Physics. He is recipient of the Commonwealth Visiting Fellowship (1984-85), at the University of Oxford, Oxford, U.K for carrying out Science & Technology Policy and Society and Government related studies, to shape the national and international development agenda. He also received Italian, Sweden, Switzerland, UNESCO, etc. scholarships for understanding the progress of science, technology and industry there. He is a well-read author and widely travelled in India and abroad. He has also delivered special lectures on Science Policy related issues to the M.Phil. and Ph.D. students at the Jawaharlal Nehru University, New Delhi. He is a Life-Member of the: Materials Research Society of India, Semi-Conductor Society of India, Association of British Scholars (British Council, New Delhi), and Oxford and Cambridge Society of India.
Keywords: Foreign Affairs Sector; Foreign Policy; International Relation